ERP Implementation at PT. Main Building Vista - Irvin Irvin; Alfred Joven; Eddy Oktarianto; Viviani Viviani; Jovianto Jovianto; Yolanda Yolanda; Charmaine Charmaine; Immanuel Zai (Universitas Muhammadiyah Makassar, 2022)
This PT. Vista Bangun Utama is a company that has engaged in construction business since 2009 in Batam City, Riau Islands. In the business process, PT. Vista Bangun Utama does not have any written system for basic operational procedures. This article aims to help PT. Vista Bangun Utama to determine the ERP system that fits the scale of the company. The ERP system Odoo can help PT. Vista Bangun Utama improve the efficiency of the enterprise through database integration such as process purchase, invoicing, expenditure and accounting